2011
DOI: 10.1002/cphc.201100713
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Biological Environments on the Electron‐Relay Functionality of Tryptophan Residues in Proteins

Abstract: Clarifying the contribution of tryptophan (Trp) to electron-transfer (ET) processes in different protein surroundings can help to understand the effective pathway of ET in proteins. Interactions between Trp residues and protein microsurroundings involve intermolecular H-bonds, cation and π-electron clouds of aromatic rings, the secondary structure and π orbital of aromatic rings, and so on. Detailed analyses reveal that the microsurroundings play an important role in modulating the electron-relay function of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Therefore, it can be speculated that a specially local microsurrounding, which can lower the redox potentials of Trp and Tyr without involving proton transfer, can also favor them to participate in electron transfer as relay stations. 24 Our recent work has revealed that the neighboring aromatic rings can facilitate the side chains of methionine (Met) or cysteine (Cys) residues to take part in electron-transfer processes by instantaneously forming lonepair (lp):π multicenter three-electron (S∴π) bonded stations in proteins. 25 In addition, we have proposed that the temporary formation of a series of lp:lp two-center three-electron bonds (O∴O, O∴S, and so on) 26 and the C-terminus of α-helices 27 can serve as the efficient relay stones to favor the long-range electron transport in proteins.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it can be speculated that a specially local microsurrounding, which can lower the redox potentials of Trp and Tyr without involving proton transfer, can also favor them to participate in electron transfer as relay stations. 24 Our recent work has revealed that the neighboring aromatic rings can facilitate the side chains of methionine (Met) or cysteine (Cys) residues to take part in electron-transfer processes by instantaneously forming lonepair (lp):π multicenter three-electron (S∴π) bonded stations in proteins. 25 In addition, we have proposed that the temporary formation of a series of lp:lp two-center three-electron bonds (O∴O, O∴S, and so on) 26 and the C-terminus of α-helices 27 can serve as the efficient relay stones to favor the long-range electron transport in proteins.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Substantively, the natural relay abilities of these two aromatic residues come from the lower redox potentials through changing their protonized states. Therefore, it can be speculated that a specially local microsurrounding, which can lower the redox potentials of Trp and Tyr without involving proton transfer, can also favor them to participate in electron transfer as relay stations . Our recent work has revealed that the neighboring aromatic rings can facilitate the side chains of methionine (Met) or cysteine (Cys) residues to take part in electron-transfer processes by instantaneously forming lone-pair (lp):π multicenter three-electron (S∴π) bonded stations in proteins .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been proposed that the neighboring amide can lower the oxidation potential of S-containing groups by formation of S–O 2c-3e bonds, which indirectly proves that the formation of a S–O 2c-3e bond can participate in the long-range electron transfer in proteins. All these reports imply that the electron relay functionality of S-containing groups may be regulated by the local neighboring environment in proteins. A similar example is that the relay ability of tryptophan residues is controlled by the local microenvironment in proteins . Because of the complexity of proteins, however, the importance of individual weak interactions in controlling the relay functionality of S-containing groups in proteins is not yet understood in detail.…”
Section: Introductionmentioning
confidence: 99%
“…A similar example is that the relay ability of tryptophan residues is controlled by the local microenvironment in proteins. 36 Because of the complexity of proteins, however, the importance of individual weak interactions in controlling the relay functionality of S-containing groups in proteins is not yet understood in detail. Motivated by these studies [1][2][3]33,34 and with the aim of exploring all the possible electron transfer pathways in proteins, in this work, we mainly examine the relay ability of S-containing groups (the side chains of Cys and Met) modulated by the adjacent aromatic amino acids through ab initio calculations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Trp also has a rich light-induced redox-type reactivity, and recently, it has been shown that Trp could be selectively modified in proteins by photoinduced electron transfer [88]. Trp is involved in electron transfer reactions through its amino group that favors or disfavors proton transfer according to the local microsurroundings and conformation changes [89]. Trp also has many synthetic analogs with interesting properties, such as the blue-colored fluorescent β-(1-azulenyl)-L-alanine, which can be biosynthetically incorporated in proteins [90].…”
Section: Discussionmentioning
confidence: 99%